Clinical-anamnestic features of mental exhaustion in medical university students - Yefimenko, S. O. (Journal of Education, Health and Sport, 2021)
In order to assess the prevalence and anamnestic features of mental exhaustion in medical university students, a clinical-anamnestic, clinical-psychopathological and psychodiagnostic study of 770 junior medical students was conducted. The results of the study revealed the prevalence of mental exhaustion among students at 54%; The most sensitive to the development of these conditions are students of the 3rd year of medical university, regardless of the specialty of study (medicine, dentistry, physical therapy, etc.), age, gender and living conditions, this may be due to the high intensity of the learning process during this period of study. The influence of mental exhaustion on the level of academic success of students is estimated – it leads to a decrease in the subjective assessment of students’ academic performance in the form of devaluation of their own success.